Does Employee’s Green Commitments and Green Attitude Mediate the Relationship of Green HRM Practices and Pro-Environmental Behaviour: Evidence from TEVT Sector Southern Punjab, Pakistan (Journal of Social Sciences Review, 2023)
This study explored how employees’ green commitments and attitudes strengthen the impact of Green Human Resource Management Practices (GHRMPs) on the Pro-environmental behavior (Pro-EB) of TEVT graduates & trainers at the workplace. The Technical Education and Vocational Training (TEVT) sector is now focusing on developing strategic, environmentally sustainable policies to develop their employee’s commitments & attitudes toward ecologically friendly activities. Using a convenient sampling technique, data was collected from 286 TEVT Trainers and TEVT graduates, and extracted results after applying PLS-SEM and Bootstrapping analysis showed that Green Human Resource Management Practices through Employee Green Commitments and Employee Green Attitude have a significant positive impact on pro-environmental behaviour. This study provides greater insight for policymakers on developing strong green commitments and attitudes among TEVT Trainers and graduates to achieve sustainable, environmentally friendly behavior at workplace and training institutes. Further in-depth analysis is therefore recommended based on PLS prediction (Q2) results by the addition of another variable.
Keywords: Pro-environmental Behaviour; Green Compensation & Rewards; Green Training & Development; Green Recruitment & Selection; Employee’s Green Attitude; Employee’s Green Commitment